Pendidikan Karakter Melalui Seni Teater Berbasis Kearifan Lokal Secara Daring untuk Anak-Anak Kampung Kumuh Pasar Keramat - Arif Sadikin Purnama; Matfa Kresna Maarifarsyah; Putri Rahayu Nengsih; Dewi Desiana; Yusuf Guntur Hari Putra; Gita Anggraini (ABDIMAS: Jurnal Pengabdian Masyarakat, 2020)
Keramat is the name of one of the markets in Sampit City which is mostly inhabited by the middle to lower economic population. Located in a congested area and market dumping waste directly into the river that flows under people's houses along with garbage that seems scattered in the river flow makes the settlement look very shabby. The children's daily activities here have to mingle with market waste and unhealthy rivers for bathing and playing. Often littering, fighting, and not caring about the environment are the daily sights of the children here. This community service is an activity of the Program Kreativitas Mahasiswa (PKM) in 2020. The focus of this activity is to instil character education for children of sacred villages by using theatre arts. Theatre is also intended to accommodate the children of the Keramat Market in developing their potential. Due to the existence of Covid-19, activities that were originally planned to be offline have turned online. The media used in carrying out activities are the WhatsApp Group, Instagram, and Youtube. Through this activity, implementation manuals have been produced, a compilation of instructional videos, cinematic audios of folk tales, and scientific articles. The children of the sacred market were enthusiastic about participating in the activity and gave positive feedback.